Desenvolvimento de um website para a realização de cálculos da estatística descritiva - SOUSA JÚNIOR, José Roberto de (2019)
This work describes the development of a website to calculate statistics on mobile and desktop devices, using development resources to provide ease of use and mobility, with the ultimate aim to aid it’s users with basic statistics calculations without detriment to the user interface or usability, regardless of the type of the user’s device. Users are able to combine and make use of quantitative and qualitative variables, helping with calculations in the field of descriptive statistics. The development will use technologies that can speed up and standardize the development, for example, Bootstrap, which consists of a set of tools to help developers build standardized responsive user interfaces that enables websites to be properly shown and used in desktops and mobile devices (tablets, smartphones, notebooks, etc.), thus preventing developers rework.